2017
DOI: 10.1016/j.clcc.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Stage IV Colorectal Cancer Survival in Younger and Older Patients

Abstract: Introduction African Americans (AA) compared to European Americans (EA) have poorer stage specific survival from colorectal cancer (CRC). Recent reports have indicated that the racial difference in survival has worsened over time, especially among younger patients. To better characterize this association, we used population-based SEER registry data to evaluate the impact of race on stage IV CRC survival in patients < 50 and ≥ 50. Patients and Methods The population was comprised of 16,782 patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…Prior studies also have shown racial differences in colon cancer survival are concentrated in younger (vs older) adults, 5,[32][33][34][35] even after adjusting for confounders, such as treatment receipt. 5,[32][33][34][35][36] Because screening has not been recommended in this younger population, the racial disparities in relative survival that we and others have observed are unlikely to be the result of differential uptake of screening. In consequence, our findings raise a number of questions concerning the contribution of treatment 37,38 and therapeutic response 39,40 to racial differences in relative survival, which also might differ for colon and rectal cancers.…”
Section: Discussionmentioning
confidence: 62%
“…Prior studies also have shown racial differences in colon cancer survival are concentrated in younger (vs older) adults, 5,[32][33][34][35] even after adjusting for confounders, such as treatment receipt. 5,[32][33][34][35][36] Because screening has not been recommended in this younger population, the racial disparities in relative survival that we and others have observed are unlikely to be the result of differential uptake of screening. In consequence, our findings raise a number of questions concerning the contribution of treatment 37,38 and therapeutic response 39,40 to racial differences in relative survival, which also might differ for colon and rectal cancers.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have reported that younger AAs have poorer prognosis than younger CAs (2, 3, 5, 31) and that the racial disparity is less pronounced in older patients. Our findings suggest a differential impact of lymphocyte score on survival in younger and older AA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the current study, we examined the differences in the lymphocyte reaction score in the colorectal cancers of AAs and CAs, and evaluated the impact on survival while adjusting for potential confounders such as age, sex, stage, treatment, and colorectal cancer tumor-related features. Because many have identified a greater survival disparity in younger AAs compared with younger CAs, we also evaluated the association of the lymphocyte score on survival by race in younger and older patients (2, 3, 4, 5, 31).…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Another study reported poorer OS in African American patients with stage IV CRC compared with European American patients, especially among those aged ≤50 years. [ 22 ] These reports suggest that racial differences affect survival in younger patients with stage IV CRC. At present, no detailed outcome data are available for other races, including Asians.…”
Section: Discussionmentioning
confidence: 99%